The historical fight for the right to care: A critique of the Mental Health Policy in Brazil - Barbara D. Nunes; Maria Isabel B. Bellini (Inkanyiso, 2022)
This article critiques the Mental Health Policy in Brazil with emphasis on the history of struggle for the right of people who have mental disorders and against violence in psychiatric institutions. The article is divided twofold; firstly, addressing exclusion, violence and exercise of citizenship, highlighting the Psychiatric Reform Movement in Brazil from 1970; secondly, contextualising the Ximenes Case with the hospital-centred model in Brazil, bringing information about the National Inspection Report in Psychiatric Hospitals. The legal framework against torture about the deprivation of liberty of people considered ‘mentally ill’ and the social division between desirable and undesirable as a characteristic of this reality. It contextualises the Mental Health Policy and the ongoing counter-reform in the Brazilian Scenario by presenting an item about the Bolsonaro Government and the attacks on Brazilian Mental Health Policy. It is pointed out in the final considerations that torture materialises in the counter-reform underway through the ‘New Mental Health Policy of Brazil’, which masks a new form of torture and suffering exposed by the structuring inequalities of capitalist society. As for the processes of resistance, the fundamental defense of community and participatory policies is pointed out in the face of challenges and complaints against human rights in institutions and logic in the Brazilian government.